Genetics of Chronic Kidney Disease Stages Across Ancestries: The PAGE Study - Lin, Bridget M.; Nadkarni, Girish N.; Tao, Ran; Graff, Mariaelisa; Fornage, Myriam; Buyske, Steven; Matise, Tara C.; Highland, Heather M.; Wilkens, Lynne R.; Carlson, Christopher S.; Park, S. Lani; Setiawan, V. Wendy; et al. (Frontiers in Genetics, 2019)
Background. Chronic kidney disease (CKD) is common and disproportionally burdens U.S. ethnic minorities. Its genetic determinants may differ by disease severity and clinical stages. To uncover genetic factors associated CKD severity among high-risk ethnic groups, we performed genome-wide association studies (GWAS) in diverse populations within the Population Architecture using Genomics and Epidemiology (PAGE) study. Methods. We assembled multi-ethnic genome-wide imputed data on CKD non-overlapping cases (4,150 mild to moderate CKD, 1,105 end-stage kidney disease [ESKD]) and non-CKD controls for up to 41,041 PAGE participants (African Americans, Hispanics/Latinos, East Asian, Native Hawaiian and American Indians). We implemented a generalized estimating equation approach for GWAS using ancestry combined data while adjusting for age, sex, principal components, study and ethnicity. Results. The GWAS identified a novel genome-wide associated locus for mild to moderate CKD nearby NMT2 (rs10906850, p=3.7 x 10-8) that replicated in the UK Biobank white British (p=0.008). Several variants at the APOL1 locus were associated with ESKD including the APOL1 G1 rs73885319 (p=1.2 x 10-9). There was no overlap among associated loci for CKD and ESKD traits, even at the previously reported APOL1 locus (p=0.76 for CKD). Several additional loci were associated with CKD or ESKD at p-values below the genome-wide threshold. These loci were often driven by variants more common in non-European ancestry. Conclusions. Our genetic study identified a novel association at NMT2 for CKD and showed for the first time strong associations of the APOL1 variants with ESKD across multi-ethnic populations. Our findings suggest differences in genetic effects across CKD severity and provide information for study design of genetic studies of CKD in diverse populations.